2010
DOI: 10.1021/jf9037419
|View full text |Cite
|
Sign up to set email alerts
|

Vinylcatechin Dimers Are Much Better Copigments for Anthocyanins than Catechin Dimer Procyanidin B3

Abstract: The binding constants (K) for the interaction of three copigments (CP), two epimeric vinylcatechin dimers (CP1 and CP2), and catechin dimer B3 (CP3) with two pigments, malvidin-3-glucoside (oenin) and malvidin-3,5-diglucoside (malvin), were determined. The K values clearly show that both vinylcatechin dimers have much higher affinity for oenin and malvin than dimer B3: K(CP2) > K(CP1) >> K(CP3). Quantum mechanics and molecular dynamics calculations were also performed to interpret the binding data and specify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 62 publications
5
28
0
Order By: Relevance
“…This is in contrast to (+)-catechin which has a trans-substituent configuration at position C-2 and C-4 in its C-ring making it non-planar, resulting in steric constraints and consequently a less favourable association with malvidin-3-glucoside (Fronczek et al, 1984;Porter, Wong, et al, 1986). In agreement with Cruz et al (2010), these data suggest that planar molecules make better copigments than non-planar molecules.…”
Section: Tablesupporting
confidence: 78%
See 1 more Smart Citation
“…This is in contrast to (+)-catechin which has a trans-substituent configuration at position C-2 and C-4 in its C-ring making it non-planar, resulting in steric constraints and consequently a less favourable association with malvidin-3-glucoside (Fronczek et al, 1984;Porter, Wong, et al, 1986). In agreement with Cruz et al (2010), these data suggest that planar molecules make better copigments than non-planar molecules.…”
Section: Tablesupporting
confidence: 78%
“…The extent to which copigment molecules stabilise the pigmented forms of the anthocyanins will depend upon their mutual interactions and this in turn will depend upon their 3-dimensional structures. Planar copigment molecules are more efficient in interacting with the anthocyanin chromophores, which are planar, than non-planar copigment molecules (Cruz et al, 2010). For those anthocyanins or anthocyanin-derived pigments that do not enter into hydration reactions there can be no measurable copigmentation, even if self-association or complexes between pigment and a potential copigment molecule exist.…”
Section: Circular Dichroism Studymentioning
confidence: 99%
“…Several authors have shown that planar substances are preferred in the formation of copigmentation complexes; since they can better stabilize the flavylium cation with their electron-rich aromatic rings when overlapping of their π-electrons with the positive charge of the flavylium cation is optimal (Cruz et al, 2010;Kunsági-Máté, Szabó, Nikfardjam, & Kollár, 2006;Lambert et al, 2011). The surrounding matrix also plays a crucial role in the stabilization of the copigmentation complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure yielded 99 papers124–222 in which a classical FF, which was not necessarily a CarbFF, was applied to a carbohydrate. Studies that considered only DNA or RNA were excluded.…”
Section: A Survey Of Recent Applicationsmentioning
confidence: 99%
“…One137 presented a simulation of an enzymatic biofuel cell. Another138 sought ways to improve pigmentation in foods. The other three studied solvated glucose in silica nanochannels,153 the elastic properties of nanomaterials with intercalated alginate,211 and the self‐assembly of alginic acid around a carbon nanotube 152…”
Section: A Survey Of Recent Applicationsmentioning
confidence: 99%